2020
DOI: 10.1515/eujal-2019-0047
|View full text |Cite
|
Sign up to set email alerts
|

Construction of difference and homogeneity: Teacher narratives about diversity in the Luxembourgish school system

Abstract: The school environment of the 21st century is shaped by rapidly changing social and societal conditions that teachers need to adapt to, increasing linguistic, cultural and ethnic diversity among other things. The development of attitudes to cope with these constant societal transformations is one of the main challenges of teacher professionalization today. In this chapter, we concentrate on the self-positioning and argumentation patterns of two Luxembourgish primary school teachers. We focus on the question ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 8 publications
(10 reference statements)
0
6
0
Order By: Relevance
“…In their narratives, teachers may express problematic issues of student diversity in relationship to their own professional identity. Wagner and Hu (2020) showed that teachers found that the diversification of Luxembourg society led to diverse classrooms. This classroom diversification was linked to a fear of marginalization-that by giving other cultures and languages too much importance and space, it was possible to lose one's own cultural traditions and thus identity.…”
Section: Diversity In Classroom Discourse Portrayed In Teachers' Storiesmentioning
confidence: 99%
See 3 more Smart Citations
“…In their narratives, teachers may express problematic issues of student diversity in relationship to their own professional identity. Wagner and Hu (2020) showed that teachers found that the diversification of Luxembourg society led to diverse classrooms. This classroom diversification was linked to a fear of marginalization-that by giving other cultures and languages too much importance and space, it was possible to lose one's own cultural traditions and thus identity.…”
Section: Diversity In Classroom Discourse Portrayed In Teachers' Storiesmentioning
confidence: 99%
“…Keith (2010) explained that black and white racial identity in schools revealed different emotional paths that must be taken before people can understand themselves and one another. Another category that the teachers in the research by Wagner and Hu (2020) used to differentiate among themselves and their students was their sociocultural background. They referred to the social environments of their students to explain their behavior and their performance at school.…”
Section: Diversity In Classroom Discourse Portrayed In Teachers' Storiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Deep-rooted values and beliefs, related for example to who belongs to an "in-group" or "out-group", have an impact on learning. They play an important role in communication and interaction in educational institutions, for both teachers (Wagner and Hu 2020) and pupils/students. The contributions by Tavares and Obojska show very clearly that experiences in early school life (such as bullying or other kinds of discrimination) are consequential and can affect self-confidence, in some cases through individuals' entire lives and professional careers.…”
Section: Migration Integration and Discriminationmentioning
confidence: 99%